Revisiting the concept of entomotoxicology - Jiri Hodecek (Forensic Science International: Synergy, 2020)
Until now, the term entomotoxicology has only been used in medico-legal sciences. However, entomotoxicology as a whole has a much wider scope and forensic entomotoxicology is just one of its branches. Based on the literature a wider definition of the term is presented. Today, we can distinguish two major branches of entomotoxicology: 1) Forensic entomotoxicology, which uses the insects as evidence of the presence of xenobiotics in decomposing tissue during an investigation and 2) Environmental entomotoxicology, which uses the insects as bioindicators of environmental pollution in non-criminal circumstances. While forensic entomotoxicology is a relatively new discipline, research in environmental entomotoxicology began as far back as the 1920s. A review of the work in entomotoxicology from the last 6 years is presented, covering several interesting new trends. This article aims to redefine entomotoxicology, which should increase awareness to bring more collaborations and multidisciplinary between related scientific fields.